THE FACTOR ANALYSIS WHICH AFFECTS DIABETIC ADHERENCE IN PHYSICAL EXERCISING AT PRAYA COMMUNITY HEALTH CENTER, CENTRAL LOMBOK - Muhamad Hasbi (poltekkes kemenkes mataram, 2017)
Abstract : the adherence of physical exercising plays important role in therapeutic management of diabetic patients. The research objective was to identify the factor which influences the adherence of diabetic patiets to exercise. The research was Quantitative research with cross sectional approach. Total sample was 122 respondents. Modifier factor data, an individual perception, and action used questionnaire. Data analysis utilized Chi Square and multiple logistic regressions. The result indicated factor which influenced the adherence of diabetic patiets to exercise was gender (p = 0026), a knowledge (p = 0.013). Benefit perceptions (p = 0.008), obstacle perceptions (p = 0.002) and family supports (p = 0.00). The most dominant factor was family supports (OR = 10.047). Therefore, it is expected that health services develop family management to improve the patients’ adherence.